1998
DOI: 10.1074/jbc.273.32.20481
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Ca2+ Binding Sites of Calmodulin Are Critical for the Regulation of Myosin Iβ Motor Function

Abstract: We coexpressed myosin I␤ heavy chain with three different calmodulin mutants in which the two Ca 2؉ -binding sites of the two N-terminal domain (E12Q), C-terminal domain (E34Q), or all four sites (E1234Q) are mutated in order to define the importance of these Ca 2؉ binding sites to the regulation of myosin I␤. The calmodulin mutated at the two Ca 2؉ binding sites in N-terminal domain and C-terminal domain lost its lower affinity Ca 2؉ binding site and higher affinity Ca 2؉ binding site, respectively. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 37 publications
10
61
4
Order By: Relevance
“…This indicates that interhead interaction is not critical for the Ca 2ϩ -dependent regulation of C442Y myosin VI. Ca 2ϩ -induced activation of the actin-activated ATPase activity has been reported for other unconventional myosins (28,(53)(54)(55)(56)(57)(58). Because bound calmodulin can be dissociated from the heavy chain at high Ca 2ϩ , it was proposed originally that the activation of the ATPase activity is because of the dissociation of calmodulin (53,56).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that interhead interaction is not critical for the Ca 2ϩ -dependent regulation of C442Y myosin VI. Ca 2ϩ -induced activation of the actin-activated ATPase activity has been reported for other unconventional myosins (28,(53)(54)(55)(56)(57)(58). Because bound calmodulin can be dissociated from the heavy chain at high Ca 2ϩ , it was proposed originally that the activation of the ATPase activity is because of the dissociation of calmodulin (53,56).…”
Section: Discussionmentioning
confidence: 99%
“…But recent studies have revealed that the inhibition does not require the dissociation of calmodulin but that Ca 2ϩ binding at the high affinity sites of calmodulin triggers the inhibition presumably because of a large conformational change of calmodulin (13,14,18). Addition of exogenous calmodulin did not rescue the inhibition of the motility activity of myosin X unless Ca 2ϩ concentration was decreased.…”
Section: Fig 13mentioning
confidence: 99%
“…The molecular mass markers used were smooth muscle myosin heavy chain (204 kDa), ␤-galactosidase (116 kDa), phosphorylase b (97.4 kDa), bovine serum albumin (66 kDa), ovalbumin (45 kDa), carbonic anhydrase (29 kDa), myosin regulatory light chain (20 kDa), and ␣-lactalbumin (14.2 kDa). The amount of the myosin X heavy chain and calmodulin was determined by densitometry as described previously (14). The steady state ATPase activity was determined by measuring liberated 32 P i at 25°C as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations